Volumetric Properties of H218O and its Mixtures with Ordinary Water - Steinberg, Paula Yael (2025)
The densities of mixtures of ordinary water and 18O-enriched water have been measured all over the range of compositions at temperatures between 293.15 and 313.15 K. The molar volumes of the mixtures exhibit a linear dependence with composition over the studied temperature range, indicating that the mixtures behave as an ideal solution. The molar volume of pure H218O has been obtained by extrapolation, accounting for the isotopic composition of the measured solutions, and the results are compared with those reported in the literature. The thermal expansion coefficient of pure H218O was also calculated over the same temperature range and is similar to that reported for ordinary water. We found that the ratio of densities of H218O and ordinary water is independent of temperature, which allows to estimate the density of H218O over an extended range of temperatures.